2021
DOI: 10.3389/fgene.2021.607910
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Molecular Mechanism of Single-Nucleotide Polymorphisms of MEG3 on Porcine Skeletal Muscle Development

Abstract: Maternally expressed gene 3 (MEG3) is a long non-coding RNA that is a crucial regulator of skeletal muscle development. Some single-nucleotide polymorphism (SNP) mutants in MEG3 had strong associations with meat quality traits. Nevertheless, the function and mechanism of MEG3 mutants on porcine skeletal muscle development have not yet been well-demonstrated. In this study, eight SNPs were identified in MEG3 of fat- and lean-type pig breeds. Four of these SNPs (g.3087C > T, g.3108C > T, g.3398C &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that exonic SNPs may affect the secondary structures of lncRNAs (Yang et al., 2021). To explore whether the three exonic SNPs of pSYISL gene could change the secondary structures of pSYISL , the RNAfold web server was used to detect the RNA secondary structures and stability of pSYISL haplotypes H1, H2 and H3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that exonic SNPs may affect the secondary structures of lncRNAs (Yang et al., 2021). To explore whether the three exonic SNPs of pSYISL gene could change the secondary structures of pSYISL , the RNAfold web server was used to detect the RNA secondary structures and stability of pSYISL haplotypes H1, H2 and H3.…”
Section: Resultsmentioning
confidence: 99%
“…The SNPs of lncRNAs can affect the function of lncRNAs and play an important role in cancer (Feng Hua et 2018;Shah et al, 2018;Tian et al, Yan et al, 2021), muscle growth (Al-Tobasei et al, 2017;Yang et al, 2021;Zhou et al, 2018), muscle fiber girth and body weight (Attaway et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs1859168, which is located in the HOTTIP (HOXA distal transcript), a lncRNA transcribed from the 5 tip of the HOXA locus, affects the expression and function of HOTTIP by reducing free energy to influence RNA secondary structure (Minotti et al, 2018). The SNP rs4081134 located in the lncRNA MEG3, influences the RNA secondary structure by decreasing free energy, which consequently affects the function of MEG3 (Yang et al, 2021). According to the RNAfold prediction, we found that plncMGPF haplotype H1 is more stable than H3.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that SNPs may change the secondary structure of lncRNA (Yang et al, 2021). We speculated that the SNPs of plncMGPF may change the secondary structures of plncMGPF.…”
Section: The Haplotypes Of Pig Lncmgpf Significantly Affect the Secondary Structures And The Rna Stabilitymentioning
confidence: 90%
“…The qRT-PCR reaction was performed by one cycle of 45°C for 15 min, one cycle of 95°C for 2 min, 40 cycles of 95°C for 10 sec, 60°C for 15 sec and 71 cycles of 60°C for 15 sec. Primers were as follows: cdk4, F 5'-TTC GAG CAT CCC AAT GTT GTC -3' and R 5'-GTC TCG ATG AAC GAT GCA GTT G -3'; cdk6, F 5'-TTG GCT TTG GTG GGT AGT TCT-3' and R 5'-TGA ATG TCG GGT AGG AAG ATT G-3'; cyclin D1, F 5'-TGC ATC TAC ACC GAC AAC TCC A -3' and R 5'-GTT GGA AAT GAA CTT CAC GTC TGT-3'; gapdh, F 5'-ATG GTG AAG GTC GGA GTG AAC-3' and R 5'-CTC GCT CCT GGA AGA TGG T-3' (Yang et al, 2021); cyclin A, F 5'-GAT TTA CAT CTT AGA AAA CAA AGG-3' and R 5'-GGT GAT CCC GCC GTC CAC T-3' (Tang et al, 2010). The 2 −ΔΔCt method was applied for Ct value analysis (Livak, Schmittgen, 2001).…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%